Urgensi pemenuhan hak dan kewajiban pekerja dalam ketenagakerjaan di indonesia sesuai pada undang – undang - Annisa pratami (Muhammadiyah Makassar University, 2023)
This study aims to provide an overview regarding the fulfillment of the rights and obligations of workers in employment in Indonesia in accordance with Law number 13 of 2003 concerning employment, because not least some of the current legislation is in a disadvantageous position in labor services and systems. industrial relations highlight very significant differences so that they are not in accordance with current developments and demands in the future. With the existence of Law number 13 of 2003 concerning employment, it is expected to be able to: uphold protection and guarantees for workers; implement national instruments on labor rights that have been ratified. The research method uses literature review with several case study methods. Research sources come from several electronic books, scientific journals and other sources whose accuracy has been confirmed by data collection techniques in the form of document studies. The results of the study show that there are still many workers whose rights and obligations are not fulfilled, so this creates problems. To overcome these problems, protection that provides legal certainty is needed.